CHARACTERISTICS OF ENDOTHELIAL DYSFUNCTION IN PATIENTS WITH AUTOIMMUNE THYROIDITIS (Multidisciplinary Journal of Science and Technology, 2025)
This article provides information on the characteristics of von Willebrand factor, endothelin-1, sICAM-1 markers that change as a result of endothelial dysfunction in patients with autoimmune thyroiditis